If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 2(3x + -2) = 6 Reorder the terms: 4x + 2(-2 + 3x) = 6 4x + (-2 * 2 + 3x * 2) = 6 4x + (-4 + 6x) = 6 Reorder the terms: -4 + 4x + 6x = 6 Combine like terms: 4x + 6x = 10x -4 + 10x = 6 Solving -4 + 10x = 6 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 10x = 6 + 4 Combine like terms: -4 + 4 = 0 0 + 10x = 6 + 4 10x = 6 + 4 Combine like terms: 6 + 4 = 10 10x = 10 Divide each side by '10'. x = 1 Simplifying x = 1
| n-23=-3 | | 6b-3=7+2b | | 76t=19 | | 2m+12=3m-17 | | 16t=12 | | 30x^2=-36x | | 18t=23 | | (5y+8)+(2n+9)= | | -9=-14x-(-21) | | b-23=23 | | -2y-6+3x=2 | | b+17=15 | | -10=a=3/3 | | 7x=1/343 | | 3z-(4-z)-4=8 | | b+1=24 | | x+5=3x-19 | | 2+5y=2x-10 | | b-12=34 | | sinx=0.51 | | a+3-2a=-5 | | 2x-4=4x+12-4-18+12x | | b-12=84 | | log^13(x^2-4)=log^13(3x) | | 3x=59 | | 3y-1=x-25 | | =(x-5z)(5x+6z) | | 3x+59=180 | | 6x+4-2x-6= | | 16=s+1 | | 9k-10k= | | x^3-7x-54=0 |